Análisis e interpretación de estados financieros para la valoración y la toma de decisiones gerenciales - Chicaiza Rogel, Briceida Liliana (2015)
The integrated project "Analysis and interpretation FINANCIAL STATEMENTS FOR THE VALUATION OF THE COMPANY AND DECISIONS GERENCIAES" is to provide adequate performance for the purpose of a financial analysis of the financial statements was made, and taking into account the company as a dynamic entity which can analyze the reality of the company. Likewise, the analysis via ratios with the ability of the company to generate liquidity, solvency and profitability are related. Also it should be a management tool and information, to collect this information verifying that accounting is reliable; after having applied the relevant analysis you get to build the conclusions that were reached, stressing that the cooperative has sufficient funds to meet its obligations to third parties, also, its structure shows that it is liquid because it has sufficient assets currents to settle their debts with less than one year.